Comparison the Efficacy of Tetracycline and Triamcinolone Mucoadhesive Gels in Recurrent Aphthous Stomatitis: A preliminary Comparative Study - Davoodvandi, Farzaneh; Soltanmohammadi, Fatemeh; Nourani, Nasim; Mahmoudi Gharehbaba, Adel; Aliakbari, Anali; Pouralibaba, Firouz; javadzadeh, Yousef (Iranian Journal of Pharmaceutical Sciences, 2025)
Recurrent Aphthous Stomatitis (RAS) is a widespread oral condition characterized by painful lesions on the oral mucosa, affecting about 20-25% of the population, with a higher occurrence in females. The etiology remains unclear, but factors such as infections, nutritional deficiencies, and stress have been implicated. Current treatments often focus on symptom relief, and while topical formulations are common, their efficacy is limited by poor retention at the site of action. This study aims to develop a mucoadhesive gel containing Tetracycline (TC) and evaluate its effectiveness compared to a Triamcinolone (Tri) gel in treating RAS. 60 participants aged between 20-50 with RAS were recruited for a randomized double-blind clinical evaluation. Two groups of patients were formed, one of which received TC-gel and the other Tri-gel. Gel formulations were prepared using carboxymethyl cellulose (CMC) and Carbopol, with pH, in vitro drug release, mucoadhesive strength, and residence time assessed. Clinical evaluations included measuring ulcer diameter, pain intensity via the Visual Analogue Scale (VAS), and patient satisfaction over a 10-day treatment period. The TC-gel demonstrated a mean pH of 6.63 and released 95.74% of TC after 240 minutes. The mucoadhesive strength was 1.59 N, with a residence time of 78 minutes. Both gels significantly reduced ulcer diameter and pain levels by day 10, with no significant differences between groups. Patient satisfaction was high, with 73% reporting excellent or good outcomes for both gels. The TC-gel is an effective treatment for RAS, comparable to Tri-gel, with promising mucoadhesive properties and patient satisfaction. These findings support the potential of TC-gel as a viable therapeutic option for managing RAS symptoms